Iron and Nickel Mixed Oxides Derived From NiIIFeII-PBA for Oxygen Evolution Electrocatalysis - Xie, Zhuohong; Zhang, Chi; He, Xin; Liang, Yi; Meng, Dingding; Wang, Jiaqi; Liang, Ping; Zhang, Zhonghua (Frontiers in Chemistry, 2019)
The sluggish kinetics of oxygen evolution reaction (OER) on anode hinders the efficiency of electrochemical water splitting. Electrocatalysts for OER based on non-precious transition metals are highly desirable. Herein, iron and nickel mixed oxides with surface oxygen vacancies were fabricated using NiIIFeII-Prussian blue analogue as the precursors by a facile two-step thermal-assisted method. The precursor compositions and calcination temperatures exert great impact on the structure and morphology of the derivatives, as well as the electrocatalytic performances for OER. Both the higher content of Ni ions during the synthesis of precursors and lower calcination temperature favor the electrocatalytic performance of the corresponding derivatives. The porous metal oxides consisting of nickel oxide and nickel ferrite exhibited the remarkable electrocatalytic property towards OER in alkaline solution, which can be attributed to the nanosized and porous structure, the co-existence of spinel NiFe2O4 and cubic NiO, the high content of surface oxygen vacancies and the low charge transfer resistance. This study will provide new inspiration for the facile design of low-cost active catalysts for OER in the future.